2017
DOI: 10.1177/2054358117714999
|View full text |Cite
|
Sign up to set email alerts
|

Changing Needs for Information and Support in an Online System for Parents of Children With Kidney Disease

Abstract: Background:Pediatric chronic kidney disease is psychologically, financially, and physically demanding on parents providing care. Parents often feel isolated because of the rarity of the condition, and geographic isolation often compounds this perception in Canada. Many parents seek assistance online for both information and social support.Objective:This study examines an online portal, titled “Ability Online,” which was designed to provide support and information to a diverse group of parents using chat facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…One important option is the initiation of online support groups that allow caregivers to ask questions, share stories, and comfort one another. Some studies have shown the effectiveness of online support groups at improving the well‐being of caregivers of sick children 31,32 . As a whole, increasing access to support groups and accurate information would likely improve SM users' online experiences and promote quality care 29,33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important option is the initiation of online support groups that allow caregivers to ask questions, share stories, and comfort one another. Some studies have shown the effectiveness of online support groups at improving the well‐being of caregivers of sick children 31,32 . As a whole, increasing access to support groups and accurate information would likely improve SM users' online experiences and promote quality care 29,33 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown the effectiveness of online support groups at improving the well‐being of caregivers of sick children. 31 , 32 As a whole, increasing access to support groups and accurate information would likely improve SM users' online experiences and promote quality care. 29 , 33…”
Section: Discussionmentioning
confidence: 99%
“…Online support groups may help reduce social and geographic isolation experienced due to the rarity of individual genetic renal conditions. 24…”
Section: Discussionmentioning
confidence: 99%
“…Online support groups may help reduce social and geographic isolation experienced due to the rarity of individual genetic renal conditions. 24 High-quality and consolidated information on their child's condition, including links to credible web sites and take-home resources to share with others were widely desired. This is a particularly important finding because limited access to appropriate resources can contribute to misinformation and increased disengagement from genetic health care services.…”
Section: Discussionmentioning
confidence: 99%
“…These have been useful in providing information, as well as fostering parental interaction, mutual support, and collaboration. 38 A final goal will be to develop a set of quality care indicators, or a “scorecard” that provides more objective measures of the transition clinic processes. 37 …”
Section: Discussionmentioning
confidence: 99%